The Acute Effects of Furosemide on Na-K-Cl Cotransporter-1, Fetuin-A and Pigment Epithelium-Derived Factor in the Guinea Pig Cochlea - Edvardsson Rasmussen, Jesper; Lundström, Patrik; Eriksson, Per Olof; Rask-Andersen, Helge; Liu, Wei; Laurell, Göran (Frontiers in Molecular Neuroscience, 2022)
Background Furosemide is a loop diuretic used to treat edema; however, it also targets the Na-K-Cl cotransporter-1 (NKCC1) in the inner ear. In very high doses, furosemide abolishes the endocochlear potential (EP). The aim of the study was to gain a deeper understanding of the temporal course of the acute effects of furosemide in the inner ear, including the protein localization of Fetuin-A and PEDF in guinea pig cochleae. Material and Method Adult guinea pigs were given an intravenous injection of furosemide in a dose of 100 mg per kg of body weight. The cochleae were studied using immunohistochemistry in controls and at four intervals: 3 min, 30 min, 60 min and 120 min. Also, cochleae of untreated guinea pigs were tested for Fetuin-A and PEDF mRNA using RNAscope® technology. Results At 3 min, NKCC1 staining was abolished in the type II fibrocytes in the spiral ligament, followed by a recovery period of up to 120 min. In the stria vascularis, the lowest staining intensity of NKCC1 presented after 30 min. The spiral ganglion showed a stable staining intensity for the full 120 min. Fetuin-A protein and mRNA were detected in the spiral ganglion type I neurons, inner and outer hair cells, pillar cells, Deiters cells and the stria vascularis. Furosemide induced an increased staining intensity of Fetuin-A at 120 min. PEDF protein and mRNA were found in the spiral ganglia type I neurons, the stria vascularis, and in type I and type II fibrocytes of the spiral ligament. PEDF protein staining intensity was high in the pillar cells in the organ of Corti. Furosemide induced an increased staining intensity of PEDF in type I neurons and pillar cells after 120 min. Conclusion The results indicate rapid furosemide-induced changes of NKCC1 in the type II fibrocytes. This could be part of the mechanism that causes reduction of the EP within minutes after high dose furosemide injection. Fetuin-A and PEDF are present in many cells of the cochlea and probably increase after furosemide exposure, possibly as an otoprotective response.